ANALISIS PERSEPSI PETANI TERHADAP PROGRAM KAWASAN RUMAH PANGAN LESTARI DI KAMPUNG DOSAI DISTRIK SENTANI BARAT KABUPATEN JAYAPURA PROVINSI PAPUA - Edison Ayakeding; Keppi Sukesi; Yayuk Yuliati (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
Papua is one of the provinces in Indonesia which has the characteristics of a different man in the business of fulfilling the needs of the family. The program of the Ministry of agriculture through community empowerment efforts to optimize the benefits of the grounds as a source of food family. Jayapura Regency is one of the areas that are also experiencing food security problems. Adequacy of food and nutrition is one of the most influential factors in producing quality human resources. The purpose of this research is to analyze the perceptions and the factors that influence the perception of farmers against the program Area Homes Preserved Food.  Research conducted in the Western County of Sentani Dosai district of Jayapura of Papua by engaging 25 respondents who implement programs KRPL in 2013. The technique of collecting data through observation method, Now as well as granting interviews specifically. Type a descriptive quantitative data. The measurement of perception of farmers using likert scale gauge. The results of the measurements indicate that the level of perception of farmers against very low KRPL program. Testing free variables using multiple linear regression analysis. The results of the analysis showed that the fulfillment of the needs and knowledge of the real effect, While the individual characteristics, experience factor farmer KRPL and support agencies have no effect on real. The value of R-sq (adj) indicates the magnitude of the influence of variables against the perception that is free of 46.83%, While the 53.17% influenced by other factors outside of this research.